Tangible-tango: Designing and fabricating tangibles with tangibles - Whiteley, B; Blagojevic, RV; Plimmer, B (Australian Computer Society, Inc, 2015)
We present Tangible-Tango, a system which enables users to fabricate new tangibles and their equivalent 3D virtual models. Thus the cognitive load required to understand and interact with virtual models is reduced. Users build new models by iteratively creating and assembling physical models. Each physical model has an associated virtual model. The new models, both virtual and tangible, can be iteratively re-used in the system. This iterative fabrication of tangibles and their virtual partners is the key contribution of Tangible-Tango. Our user study found that all participants efficiently produced the desired results, regardless of their background. This indicates the system is easy to learn and takes us one step closer to melding tangible and virtual 3D representations.
Keywords: tangible user interface, TUI, tangible interaction, fabrication.